Investigation of graphene oxide-aluminium oxyhydroxide as effective adsorbent for fluoride removal and its fabrication as free-standing membrane - Tan, Su-En (2025)
Water is a vital resource essential for the survival of all living organisms, supporting critical human functions. One of the most dangerous contaminants in water is the presence of high fluoride ions found in both natural and industrial water sources. The use of Graphene Oxide (GO) as the backbone of new materials has been studied and most of them produced promising result with high efficiency of fluoride adsorption. The use of Graphene Oxide- Aluminium Oxyhydroxide (GO-AlO(OH)) in defluorination study had showed promising results compared to other alternatives used. This study investigate the efficiency of GO-AlO(OH) with aluminium hydroxide (Al(OH)3) and successfully showed comparable results. The study showed the amorphous nature of GO-AlO(OH) and Al(OH)3 in which the aluminium oxyhydroxide (AlO(OH)) compound can be seen on surface of GO. Energy Dispersive X-Ray Spectroscopy (EDXS) was carried out to support the presence of Aluminium in GO-AlO(OH) sample and its purity with comparison of ideal ratio and experimental ratio for both GO-AlO(OH) and Al(OH)3. X-Ray Diffraction Spectroscopy (XRD) analysis showed the amorphous state of GO and interfered the intensity of the AlO(OH) peaks. The broad bumps around 18°, 20° and 38° suggested the state of Al(OH)3 which could be a bayerite. During the analysis of fluoride removal adsorption, the GO-AlO(OH) and Al(OH)3 showed comparable results with over 90% from overall percentage. However, both adsorbents showed signs of agglomeration of particles or saturation of the adsorption site. The study also showed that the increase in concentration of fluoride decreases the efficiency of adsorbent for fluoride removal. The Fourier Transform Infrared Spectroscopy (FTIR) showed a slight shift of peaks due to the interaction of metal ions with the hydroxyl group and presence of clusters of amorphous alumina in GO-AlO(OH) when compared to GO. The interaction of fluoride and GO-AlO(OH) follows the chemisorption process with high R2 value of PSO and shows distortion of peaks at fingerprint region with FTIR. The unique characteristics of GO-AlO(OH) have led to the discovery of the fabrication of free standing GO-AlO(OH) membrane for potential removal of fluoride ion by filtration process. The successful formation of free-standing GO-AlO(OH) membrane is due to its layered structure, strong interlayer bonding through van der Waals forces, hydrogen bonding, and electrostatic interactions.